The Role of Islamic Education as the First Step Moral Education in Era Society 5.0: Implications for Indonesian and Turkish Education Systems - Syamsul Huda; Nur Ahid; Hasan Said Tortop; Fitria Lestari; Andika Eko Prasetiyo (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Technological developments in the industrial era 4.0 are the initial problems that will trigger further problems in the era of society 5.0. Preparations for the era of society 5.0 must be carried out and designed earlier in anticipation of moral decline due to current technological developments. The complexity of the moral decline is an integral part of the education system. In this research, an integrated study of the Islamic education system of two countries, namely Indonesia and Turkey, was carried out to find important points as a solution to problems to face the era of society 5.0. The research method was carried out using 2 sources, namely observational studies of data collection with interview techniques (quantitative) and literature studies in accordance with the discussion of the challenges of Islamic education in facing society 5.0 (qualitative). Approach analysis using Structural Equation Modeling (SEM) was carried out to strengthen the results. The results of the research as the findings in this article obtain information that respect for others, politeness in speech, and manners in acting must be applied to primary to junior secondary education. All moral education must be based on Islamic education by using innovative learning models as an effective education system in the era of society 5.0. Keywords: Islamic Education, Moral Education, Education in Era Society 5.0